Uji Sitotoksik Ekstrak Etanol, Fraksi Polar, Semipolar Dan Nonpolar Herba Kemangi (Ocimum Sanctum L.) Terhadap Sel T47d - Puspitaningrum, Rizki Awalia, Maryati, Ph.D., Apt (2016)
Previous experiment indicated broad spectrum biological activity of Basil (Ocimum sanctum L.) ie anticancer, antibacterial, and antioxidant. This experiment aimed to determine the cytotoxic effects of ethanol extract 96%, polar, semipolar, and nonpolar fraction Basil (Ocimum sanctum L.) on T47D cells and to know the compounds contained in herbs basil as well as the fraction of the best cytotoxic activity. Extraction was conducted by maceration method using ethanol extract 96%. The ethanolic extract fractionated by using liquid partition. The content of the compounds in the extract and the fractions were identified using Thin Layer Chromatography (TLC) with various spray reagent. Cytotoxic test performed by using MTT assay method to obtain IC50 values. This experiment conclude IC50 of ethanol extract 96%, n-hexane, chloroform, and ethyl acetate fraction were IC50 >250 µg/mL, >250 µg/mL, 36,98 µg/mL, and >250 µg/mL respectivly. Chloroform fraction has the strongest effect anticancer. TLC test results show that the ethanol extract of the herbs basil contain the class of flavonoids, terpenoids, saponins, alkaloids and phenolic. Chloroform fraction containing class of flavonoids, terpenoids, alkaloids and phenolic.